2014
DOI: 10.1177/0194599814541627a312
|View full text |Cite
|
Sign up to set email alerts
|

SNOT‐22 in a Control Population

Abstract: Objectives: To assess SNOT-22 and its subscales in a nonrhinosinusitis UK-wide population. Design: Self-reported questionnaire. Setting: Based from 30 ENT departments around the UK. Participants: 250 Non-rhinosinusitis adultsno selfreported nasal problems in the past, no chronic conditions undergoing active treatment and no hospital admissions in the preceding 12 months. Main outcome measures: SNOT-22, SF-36. a Members of the "CRES Group" are presented in Appendix 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…Twenty‐two items are covered and scored on a Likert grading system (0‐5). The resulting scores range from 0 to 110, and the median score in a normal population without CRS ranges between 6.5 and 7 in published studies …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐two items are covered and scored on a Likert grading system (0‐5). The resulting scores range from 0 to 110, and the median score in a normal population without CRS ranges between 6.5 and 7 in published studies …”
Section: Methodsmentioning
confidence: 99%
“…The resulting scores range from 0 to 110, and the median score in a normal population without CRS ranges between 6.5 and 7 in published studies. 3,8,15 The SF-12 questionnaire (a condensed version of the SF-36) is a The EQ-5D-5L is a standardised measure of health status consisting of a visual analogue scale (VAS) to assess patient-reported health state on the day of completing the survey (0=worst imaginable health state and 100=best imaginable health state) in addition to a questionnaire with five dimensions (mobility, self-care, usual activities, pain/discomfort and anxiety/depression) (EuroQol 2011). 16 Each of the dimensions asks for a response that corresponds to a health status level of no problems, slight problems, moderate problems, severe problems and extreme problems that are coded level 1-5, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although we did not explicitly identify CRS in our patient population, our findings indicate that worse SNOT‐22 scores correlated with worsened pulmonary health in CF patients. Other studies have demonstrated that patients without sinonasal pathology have an average SNOT‐22 score of 12.0 . Among our study population, baseline patients had an average SNOT‐22 score of 25.4, whereas exacerbation patients had an average score of 38.4.…”
Section: Discussionmentioning
confidence: 68%
“…All control subjects were students from the university affiliated with the hospital (University College London) and underwent a full clinical evaluation which required a normal clinical history, normal nasal endoscopy (NE) evaluation, negative allergy tests and a SNOT 22 score of less than 10 30 to exclude AR, CRS, DNS, or any other sinonasal disease.…”
Section: Methodsmentioning
confidence: 99%
“…A patient's clinical diagnosis was based on the clinical history, nasendoscopic (NE) evaluation, computerized tomography (CT) findings, allergy tests along with SNOT‐22 scores (a score of more than 10) 30,31 . Skin prick tests were used to diagnose allergic rhinitis as per the British Society of Allergy and Clinical Immunology guidelines 32 …”
Section: Methodsmentioning
confidence: 99%